2007
DOI: 10.1080/02770900601182517
|View full text |Cite
|
Sign up to set email alerts
|

Improved Health Outcomes with Peak Flow Monitoring for Children with Asthma

Abstract: PFM significantly reduced pediatric asthma morbidity in this sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…One study found that patients who used PEF to guide therapy when symptomatic had a lower asthma severity score, fewer symptom days and less healthcare utilisation than children who either used PEF daily or evaluated subjective symptoms alone [37]. In an uncontrolled study, in 77 asthmatic children, daily PEF in combination with comprehensive asthma education resulted in a reduction in the number of asthma episodes, medical and emergency department visits, and missed school days [38]. Two randomised controlled studies did not show a benefit of PEF guided treatment compared with management based on symptoms alone, and addition of PEF did not enhance self-management even during acute exacerbations [28,39].…”
Section: Measurement Of Peak Flowmentioning
confidence: 99%
“…One study found that patients who used PEF to guide therapy when symptomatic had a lower asthma severity score, fewer symptom days and less healthcare utilisation than children who either used PEF daily or evaluated subjective symptoms alone [37]. In an uncontrolled study, in 77 asthmatic children, daily PEF in combination with comprehensive asthma education resulted in a reduction in the number of asthma episodes, medical and emergency department visits, and missed school days [38]. Two randomised controlled studies did not show a benefit of PEF guided treatment compared with management based on symptoms alone, and addition of PEF did not enhance self-management even during acute exacerbations [28,39].…”
Section: Measurement Of Peak Flowmentioning
confidence: 99%
“…Developed through collaboration between an asthma educator, the health care provider, and the family, action plans have been shown to be of value in older children [105][106][107][108] , although they have not been sufficiently studied in this younger age group. An asthma action plan should contain details that will enable those who care for the child to recognize exacerbations early, and know what interventions are required, including when medical help should be sought.…”
Section: Home Action Plan For Family/caregiversmentioning
confidence: 99%
“…When children reach adolescence, they find it more difficult to manage their chronic illnesses. Despite advances in medical technologies in the diagnosis and treatment of asthma, these medical technologies need to be accepted and understood by patients so that they can adhere to the medical regimens prescribed for them (Burkhart, Rayens, Revelette, & Ohlmann, 2007; Lim, Wood, & Miller, 2008; Osterberg & Blaschke, 2005; Sokol, McGuigan, Verbrugge, & Epstein, 2005). In many cases, asthma control relies more on the lifestyle management that helps to control the allergic sources than on the medications alone (Global Initiative for Asthma [GINA], 2007; Madge, McColl, & Paton, 1997; National Heart, Lung, and Blood Institute, 2007; Wolf, Guevara, Grum, Clark, & Cates, 2002).…”
mentioning
confidence: 99%